Utilization of Sludge from Cow Dung Biogas as Additional Feed for Sangkuriang Catfish (Claries gariepinus) - Dina Dyah Saputri; Sri Wahyuni; Alfiia Rahma Daani (Universitas Diponegoro, 2024)
Catfish farming is often faced with the availability of feed which is relatively expensive, so it is necessary to find a solution to support the catfish farming business—provision of sufficient and good quality feed to support fish growth. This study aimed to determine the level of sludge suitable for use as additional feed. Observations were made using the experimental method with a Randomized Block Design (RBD) research design involving one control group and three treatment groups with three repetitions each. The parameters observed were length (p), width (l), and fish weight (b). The environmental parameters observed were water temperature and pH. The results showed that the best sludge presentation to be given as additional feed was in treatment 1 with an average weight between 71.33-73.75 grams, an average length ranging from 18.13 to 22.17 cm, and a width of 3.16. – 3.27 cm. Survival Rate is between 275-78%. Specific Growth Rate (SGR) 1%. Specific Weight Growth Rate (SWGR) is between 2-3%. Based on the results, this study recommends that in the use of biogas output sludge as pellets, it is necessary to improve the quality of feed by adding good nutritious ingredients for catfish.